The impact of internal parasitism on milk production and udder health of dairy goats in low-input pastoral farming systems in Greece - V. Papanikolopoulou; A. I. Gelasakis; E. Papadopoulos; S. Vouraki; A. Soufleri; G. Arsenos (Parasitology Research, 2026)
Abstract Parasitic infections are a major constraint to ruminant productivity; however, their impact on dairy goats—particularly under low-input pastoral systems—remains poorly quantified, and the effects of cestode and lungworm infections on milk production and udder health have not been previously evaluated. This study assessed the effects of gastrointestinal nematodes (GIN), cestodes, and lungworms on milk production and udder health in dairy goats reared under low-input pastoral systems. A total of 294 goats from three breeds across seven farms in Central and Northern Greece were monitored over two consecutive milking periods. Parasitic burden was assessed monthly alongside milk yield, composition traits, and udder health indicators. The effects of individual parasite group infections (GIN, cestodes, and lungworms), overall infection status (presence of at least one parasite group), specific parasite co-infection patterns, and GIN faecal egg counts were evaluated using linear mixed-effects models. Parasitism significantly affected ( P < 0.05) milk yield and composition. GIN infection was associated with reductions in milk yield (2.8–7.6%), protein content (1.2–2.4%), protein yield (3.7–7.5%), SNF content (0.4–1.0%), and SNF yield (2.2–6.2%). Similarly, overall infection status was associated with reductions in milk yield (2.23–6.17%), protein content (0.61–1.79%), protein yield (3.74–7.46%), lactose yield (2.18–6.22%), and SNF yield (2.46–6.34%). No significant effects were detected for the evaluated parasite co-infection patterns, GIN faecal egg counts, somatic cell counts, or total viable counts. These findings demonstrate that internal parasitism can impair dairy goat productivity without evident effects on udder health, highlighting the importance of targeted parasite control strategies in low-input systems.